A chemically reduced graphene oxide–Au nanocage composite for the electrochemical detection of dopamine and uric acid. Issue 25 (15th June 2017) - Li, Weihao; Ma, Lian; Wu, Bingxue; Zhang, Yue; Li, Zhuang
Abstract : Herein, a chemically reduced graphene oxide–Au nanocage (CRGO–AuNCs) composite was synthesized by electrostatic assembly of poly-diallyldimethylammonium chloride (PDDA)-modified CRGO and mercaptosuccinic acid (MSA)-modified Au nanocages. Abstract : Herein, a chemically reduced graphene oxide–Au nanocage (CRGO–AuNCs) composite was synthesized by electrostatic assembly of poly-diallyldimethylammonium chloride (PDDA)-modified CRGO and mercaptosuccinic acid (MSA)-modified Au nanocages. The product was characterized via AFM, TEM, EDS, and XRD. CRGO–AuNCs were then used to prepare an electrochemical sensor for the simultaneous detection of dopamine (DA) and uric acid (UA). Electrochemical investigations indicated that CRGO–AuNCs exhibited high peak currents for the oxidation of DA and UA. The composite-modified glass carbon electrode (CRGO–AuNC/GCE) displayed good selectivity and wide linear ranges for the simultaneous detection of DA (5–250 μM) and UA (5–150 μM).